Comparative genomics of host-specialized populations of Corynespora cassiicola causing target spot epidemics in the southeastern United States - Dacones, Leilani S.; Kemerait, Robert C.; Brewer, Marin T. (Frontiers in Fungal Biology, 2022)
Numerous plant-pathogenic fungi secrete necrotrophic effectors (syn. host-selective toxins) that are important determinants of pathogenicity and virulence in species that have a necrotrophic lifestyle. Corynespora cassiicola is a necrotrophic fungus causing emerging target spot epidemics in the southeastern United States (US). Previous studies revealed that populations of C. cassiicola from cotton, soybean, and tomato are clonal, host specialized and genetically distinct. Additionally, cassiicolin – the necrotrophic effector identified in some C. cassiicola isolates – is an important toxin for virulence on rubber. It is encoded by seven Cas gene variants. Our goal was to conduct comparative genomic analyses to identify variation among putative necrotrophic effector genes and to determine if lack of one of the mating-types explained clonal populations in C. cassiicola causing outbreaks in the southeastern US and the apparent absence of sexual reproduction worldwide. A total of 12 C. cassiicola genomes, with four each from isolates from tomato, soybean, and cotton, were sequenced using an Illumina Next Seq platform. Each genome was assembled de novo, compared with the reference genome from rubber, and searched for known Cas, and other gene clusters with homologs of secondary metabolites. Cas2 and/or Cas6 were present in isolates from soybean in the southeastern US, whereas Cas1 and Cas2 were present in isolates from cotton in the southeastern US. In addition, several toxin genes, including the T-toxin biosynthetic genes were present in all C. cassiicola from cotton, soybean, and tomato. The mating-type locus was identified in all of the sequenced genomes, with the MAT1-1 idiomorph present in all cotton isolates and the rubber isolate, whereas the MAT1-2 idiomorph was present in all soybean isolates. We developed a PCR-based marker for mating-type in C. cassiicola. Both mating types were present in isolates from tomato. Thus, C. cassiicola has both mating-types necessary for sexual reproduction, but the absence of both mating-types within soybean and cotton populations could explain clonality in these populations. Variation in necrotrophic effectors may underlie host specialization and disease emergence of target spot on cotton, soybean, and tomato in the southeastern US.